Between the Olympian and the Dionysian: Pagan Energy in Paintings by Frederic Leighton and Lawrence Alma-Tadema - Anne-Florence Gillard-Estrada (Cahiers Victoriens et Edouardiens)
This article aims at examining the tension that characterizes some representations of Antiquity in the works of British painters of the 1860s-1890s as well as the critical reception of those works in contemporary periodicals and monographs. The artists who revived the subjects and forms of Antiquity have been labelled as ‘Classical Painters’ and ‘Olympians’ because of their supposed idealization of Antiquity. And yet the term ‘Olympian’ is highly problematic as it evacuates the ambivalence that characterizes that painting. Such taxonomy indeed evokes the Apollonian while precluding the Dionysian dimension that is in fact present in some of their representations of the antique body. This article first draws on examples taken from Frederic Leighton’s production to show the conflict between the Greek ideal as propounded by the neo-Winckelmannian aesthetic and academic tradition and a more controversial vision of Greek culture exploring more unconventional aspects of paganism. Leighton was in fact deeply influenced by Walter Pater’s revision of Greek culture. Lawrence Alma-Tadema also aimed at exploring the pagan and Dionysian dimensions in his own representations of rituals. The return to Greece in painting was therefore riddled with contradictions, but it contributed to the re-definition of the aesthetics associated with Antiquity.